Promoting conservation culture through exchange in training on traditional and contemporary lining methods - Maria Aguiar; Nico Broers; Olivier Verheyden; Antonio Iaccarino Idelson; Paolo Roma; Ana Cudell (CeROArt : Conservation, Exposition, Restauration d'Objets d'Art)
Conservation training is much influenced by the culture context in which it is developed. Depending on the country of origin, structural treatment of canvas paintings widely varies, reflecting climate conditions but also training traditions. Via an Erasmus Programme, traditional and contemporary lining techniques used in Belgium, Italy and Portugal were compared, bringing together teachers and students from École Supérieure des Arts Saint-Luc de Liège, the Universitá degli Studi Urbino “Carlo Bo” from Urbino and the Escola das Artes, Universidade Católica Portuguesa.